Social problems of military retirees in the Emirate of Dubai - Altamimi, Noora Ahmed; Al-Madani, Khalil (Al-Adab Journal, 2022)
This study aimed at the most important social problems faced by military retirees in the Emirate of Dubai, by identifying the most important social problems for retirees from the research sample, and it tried to answer the following questions: 1- The most important social problems in the social aspect of military retirees in the Emirate of Dubai, 2- The most important problems related to the economic aspect of military retirees in the Emirate of Dubai, a benefit from his military experiences in the Emirate of Dubai, 3- The most important issues related to the health aspect in the Emirate of Dubai, 4-The view of the military retiree in the Emirate of Dubai towards the possibility of benefiting from his scientific and practical experiences after retirement. To achieve these goals, the social survey approach was applied, through a questionnaire that was applied to a purpose sample consisting of (151) respondents from military retirees in the Emirate of Dubai, in addition in-depth interviews with 10 military retirees from the Emirate of Dubai.The results of the study showed that the majority of the sample were males who did not exceed fifty years, and did not exceed the secondary stage of their education, and the reasons for retirement were arranged as follows: reaching the retirement stage, then health reasons, then early retirement with a personal desire. The results of the study also revealed that retirees The military in the Emirate of Dubai suffers from multiple problems, including: First, social problems: family disputes increased after retirement, increased leisure time after retirement, and not joining a sports or social club. Secondly, the economic problems represented in: the insufficient retirement pension to meet the needs of the retiree and his family’s necessary needs, and that their working children do not contribute to spending on the family, and they had to borrow from the bank after retirement, thirdly, the health problems represented in: their health condition worsened after retirement, and the suffering from a chronic disease.